Challenge and Development Strategy for Colon-Targeted Drug Delivery System - Iswandana, Raditya; Putri, Kurnia Sari Setio; Putri, Fathia Amalia; Gunawan, Maxius; Larasati, Sekar Arum (Pharmaceutical Sciences and Research, 2022)
Colon-Targeted Drug Delivery System (CTDDS) is able to improve local therapeutic effects in the treatment of colon-specific diseases, such as Crohn’s disease, Ulcerative Colitis (UC), and Irritable Bowel Syndrome (IBS). A colon can also be a suitable site for systemic delivery of drugs susceptible to extreme gastric pH, such as peptides and protein therapeutics. The physiological conditions of the gastrointestinal tract and the physicochemical properties of drugs are being considered to develop strategies and approaches to overcome emerging challenges. This review will discuss factors, challenges, strategies, and approaches to developing a colon-targeted drug delivery system.